2006
DOI: 10.1242/jcs.03055
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SRC as a key PKA-stimulated tyrosine kinase involved in the capacitation-associated hyperactivation of murine spermatozoa

Abstract: Fertilization of the mammalian oocyte depends on the ability of spermatozoa to undergo a process known as capacitation as they ascend the female reproductive tract. A fundamental feature of this process is a marked increase in tyrosine phosphorylation by an unusual protein kinase A (PKA)-mediated pathway. To date, the identity of the intermediate PKA-activated tyrosine kinase driving capacitation is still unresolved. In this study, we have identified SRC as a candidate intermediate kinase centrally involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
164
3
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(192 citation statements)
references
References 58 publications
15
164
3
10
Order By: Relevance
“…It has been shown in other cell types that gelsolin can be phosphorylated by c-SRC on tyrosine 438 resulting in its release from actin filaments (19). In human sperm, SRC is involved in regulating sperm capacitation, calcium fluxes, tyrosine phosphorylation, and the AR (20,37,38). Previous studies indicated that SRC is not directly involved in tyrosine phosphorylation but rather inhibits protein phosphatase resulting in an increase of protein tyrosine phosphorylation (39).…”
Section: How Is Gelsolin Activity Inhibited During Spermmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in other cell types that gelsolin can be phosphorylated by c-SRC on tyrosine 438 resulting in its release from actin filaments (19). In human sperm, SRC is involved in regulating sperm capacitation, calcium fluxes, tyrosine phosphorylation, and the AR (20,37,38). Previous studies indicated that SRC is not directly involved in tyrosine phosphorylation but rather inhibits protein phosphatase resulting in an increase of protein tyrosine phosphorylation (39).…”
Section: How Is Gelsolin Activity Inhibited During Spermmentioning
confidence: 99%
“…Moreover, it was shown that capacitation is regulated by two parallel pathways. The first one requires activation of protein kinase A leading to SRC activation, and the second one involves the inactivation of Ser/Thr phosphatases (37,40). SRC is also found in the sperm flagellum and head and is localized to membrane fraction (40).…”
Section: How Is Gelsolin Activity Inhibited During Spermmentioning
confidence: 99%
“…Baker et al [52] reported that PKA catalytic subunit can be immunodetected in the flagellar fraction of mouse spermatozoa, but barely in the head fraction. Our results in this study (Fig.…”
Section: Interaction Between Pka and Calyculin A-sensitive Protein Phmentioning
confidence: 99%
“…A variety of factors, including Ca 2ϩ , HCO 3 Ϫ , and H 2 O 2 stimulate soluble adenylyl cyclase leading to increased cytosolic levels of cAMP (4). This increase in cAMP then activates PKA, and the consequence is a significant increase in tyrosine phosphorylation of protein substrates localized in the flagellum such as AKAP3, AKAP4, CABYR, hsp-90, ODF2, and tubulin (3,(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%